2018
DOI: 10.3390/nano9010004
|View full text |Cite
|
Sign up to set email alerts
|

A Colorimetric Enzyme-Linked Immunosorbent Assay with CuO Nanoparticles as Signal Labels Based on the Growth of Gold Nanoparticles In Situ

Abstract: A colorimetric immunoassay has been reported for prostate-specific antigen (PSA) detection with CuO nanoparticles (CuO NPs) as signal labels. The method is based on Cu2+-catalyzed oxidation of ascorbic acid (AA) by O2 to depress the formation of colored gold nanoparticles (AuNPs). Specifically, HAuCl4 can be reduced by AA to produce AuNPs in situ. In the presence of target, CuO NPs-labeled antibodies were captured via the sandwich-type immunoreaction. After dissolving CuO nanoparticles with acid, the released … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 27 publications
(36 reference statements)
1
14
0
Order By: Relevance
“…For example, Cu II is a paramagnetic species whereas Cu I is a diamagnetic species. Based on this spectroscopic advantage, Cu II -ATCUN state has been studied extensively as a paramagnetic probes and sensors ( Donaldson et al., 2001 ; Maiti et al, 2017b ; Deng et al., 2019a , 2019b ; Torrado et al., 1998 ). Significantly, this review is mainly focused on stable Cu II -ATCUN derivatives as spectroscopic probe and positron emission tomography (PET) imaging ( Miyamoto et al., 2016 ).…”
Section: Applications Of M-atcun Derivativesmentioning
confidence: 99%
See 3 more Smart Citations
“…For example, Cu II is a paramagnetic species whereas Cu I is a diamagnetic species. Based on this spectroscopic advantage, Cu II -ATCUN state has been studied extensively as a paramagnetic probes and sensors ( Donaldson et al., 2001 ; Maiti et al, 2017b ; Deng et al., 2019a , 2019b ; Torrado et al., 1998 ). Significantly, this review is mainly focused on stable Cu II -ATCUN derivatives as spectroscopic probe and positron emission tomography (PET) imaging ( Miyamoto et al., 2016 ).…”
Section: Applications Of M-atcun Derivativesmentioning
confidence: 99%
“…Over the last few decades, the research on designed metal-ATCUN derivatives (ATCUN; amino terminal copper and nickel binding motif possessing H 2 N–X-X-His sequence; X = any amino acid) has greatly progressed due to the wide range of applications envisaged, relevant for biology and chemistry, which include DNA ( Harford and Sarkar, 1997 ; Mack and Dervan, 1992 ; Jin and Cowan, 2005 , 2007 ; Agbale et al., 2016 ; Yu and Cowan, 2017a , 2017b ; Gonzalez et al., 2018 ), RNA ( Yu and Cowan, 2017a , 2017b ; Gonzalez et al., 2018 ; Ross et al., 2017 ), proteins ( Agbale et al., 2016 ; Yu and Cowan, 2017a , 2017b ; Gonzalez et al., 2018 ; Pinkham et al., 2018a , 2018b ), sugar ( Yu and Cowan, 2017a , 2017b ), and lipids cleavage ( Alexander et al., 2017 ), antitumor ( Kimoto et al., 1983 ), and antimicrobial activity ( Alexander et al., 2018 , 2019 ), inhibition of enzyme activity ( Gokhale et al., 2008 ), telomere shortening ( Yu et al., 2015 ), aggregation of amyloid-β peptides ( Zhang et al., 2016 ), nitration of tyrosine ( Maiti et al., 2019 ), protein-protein cross-linking ( Horowitz et al., 2012 ; Brown et al., 1998 ), water oxidation ( Deng et al., 2018 ), hydrogen evolution ( Kandemir et al., 2016 ), nitrite to NH 3 ( Guo et al., 2018 ), useful in spectroscopic probes ( Donaldson et al., 2001 ; Maiti et al, 2017b ; Deng et al., 2019a , 2019b ; Torrado et al., 1998 ), and imaging ( Miyamoto et al., 2016 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lai’s group developed a colorimetric immunoassay for CEA detection based on a copper chromogenic reaction, in which Cu(II) released from CuO NPs coordinates with a synthesized chromogenic of 1,2-diphenyl-2-(2-(pyridin-2-yl)hydrazono)ethanone, together with the colorimetric signal change from colorless to red [164]. We have demonstrated that the released Cu(II) from the captured CuO NPs labels can catalyze the oxidation of AA by O 2 , thus depressing the AA-guided formation of colored AuNPs [165]. The colorimetric assay with an LOD of 0.05 ng/mL showed good applicability for the assay of PSA in serum samples.…”
Section: Chromogenic Reactions Induced By the Constituent Elementsmentioning
confidence: 99%